PENDIDIKAN AKHLAK DALAM NOVEL AYAT-AYAT CINTA - Ibrohim, Achmad; Maulia, Naufa; Yunus, Syarifudin (Cahaya Ilmu Bangsa Institute, 2025)
In the modern era full of moral challenges, literature is present as an effective means to instill moral values. One of the literary works that contains a strong moral message is the novel Ayat-Ayat Cinta by Habiburrahman El Shirazy. This study aims to reveal the forms of moral education contained in the novel using qualitative descriptive methods and content analysis. The results of the study show that this novel is full of Islamic moral values ​​that are reflected through the characters, plot, and story conflicts. Values ​​such as honesty, patience, responsibility, sincerity, and respect for others are the main focus. The character Fahri is described as a personal representation of Muslim ideals who is able to be a role model in calmness and action. Therefore, Ayat-Ayat Cinta not only functions as a work of entertainment, but also as a medium for inspiring and relevant moral learning, especially for the young generation of Muslims. This research is expected to be a contribution to the development of character education through literary works.